High frequency of NAT2 slow acetylator alleles in the Malay population of Indonesia: an awareness to the anti-tuberculosis drug induced liver injury and cancer (Faculty of Medicine Universitas Indonesia, 2017)
Background: Arylamine N-acetyltransferase 2 (NAT2) polymorphism was previously reported to have association with the risk of drug toxicities and the development of various diseases. Previous research on the Indonesian population, especially Javanese and Sundanese, showed that there were 33% NAT2 slow acetylator phenotype. The aim of this study was to map the NAT2 variation in the Malay ethnic to gain a deeper insight into NAT2 haplotypic composition in this ethnic.Methods: 50 healthy samples from the Indonesian Malay ethnic were obtained. They were interviewed about their ethnic backgrounds for the last three generations. DNA was extracted from peripheral blood and NAT2 genotyping was done using the PCR direct Sequencing. Data were compiled according to the genotype and allele frequencies estimated from the observed numbers of each specific allele. Haplotype reconstruction was performed using PHASE v2.1.1 software.Results: We found 7 haplotypes consisting of 6 SNPs and 14 NAT2 genotype variations in Indonesian Malay population. The most frequent allele was NAT2*6A (38%) which was classified as a slow acetylator allele. According to bimodal distribution, the predicted phenotype of the Malay population was composed of 62% rapid acetylator and 38% slow acetylator. According to trimodal distribution, the predicted phenotypes for rapid, intermediate and slow acetylators were 10%, 52% and 38% respectively.Conclusion: Our result indicates the presence of the allelic distribution and revealed the most frequent acetylator status and phenotype for the Indonesian Malay population. The result of this study will be helpful for future epidemiological or clinical studies and for understanding the genetic basis of acetylation polymorphism in Indonesia.